Answer:
(x, y) = (7, 4)
Step-by-step explanation:
I find a graphing calculator to give a solution quickly and easily.
(x, y) = (7, 4)
__
Here, we can solve the first equation for x, then substitute into the second.
x = 23 -4y
-2(23 -4y) +3y = -2 . . . . . substitute for x
-46 +8y +3y = -2 . . . . . eliminate parentheses
11y = 44 . . . . . . . . . . . collect terms
y = 4 . . . . . . . . . . . . divide by the coefficient of y
x = 23 -4·4 = 7 . . . . use the expression for x to find x
(x, y) = (7, 4)